1980
DOI: 10.3758/bf03198819
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental frequency as a cue to postvocalic consonantal voicing: Some data from speech perception and production

Abstract: Several recent studies by Lehiste have reported that changes in fundamental frequency (FO) can serve as a cue to perceived vowel length and, furthermore, that the perceived lengthening of the vowel can influence perception of the voicing feature of stop consonants in syllable-final position. In Experiment 1, we replicated Lehiste's basic results for stop consonants in final position. Experiment 2 extended these results to postvocalic fricatives. The final consonant in syllables of intermediate vowel duration w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 12 publications
1
19
0
1
Order By: Relevance
“…This research has shown that steadystate vowel duration, or perhaps the ratio of fricative-tovowel duration, is a strong cue for the voicing contrast in word-final fricatives (Denes, 1955;Derr and Massaro, 1980;Gruenenfelder and Pisoni, 1980). The duration of the steadystate vowel, or of the nasal resonance in final nasal-stop clusters, also provides su•cient voicing cues for final stops (Raphael, 1972; Raphael et al, 1975;Raphael et al, 1980).…”
mentioning
confidence: 95%
“…This research has shown that steadystate vowel duration, or perhaps the ratio of fricative-tovowel duration, is a strong cue for the voicing contrast in word-final fricatives (Denes, 1955;Derr and Massaro, 1980;Gruenenfelder and Pisoni, 1980). The duration of the steadystate vowel, or of the nasal resonance in final nasal-stop clusters, also provides su•cient voicing cues for final stops (Raphael, 1972; Raphael et al, 1975;Raphael et al, 1980).…”
mentioning
confidence: 95%
“…For higher f 0's, listeners more often report hearing voiceless consonants ͑i.e., ͓pa͔͒. This finding is extremely robust, and has been reported across multiple phonetic contexts, using a variety of measures ͑e.g., Chistovich, 1969;Haggard et al, 1970;Fujimura, 1971;Cohen, 1976, 1977;Derr and Massaro, 1980;Gruenenfelder and Pisoni, 1980;Haggard et al, 1981;Kohler, 1985;Kohler and van Dommelen, 1986;Whalen et al, 1993;Castleman and Diehl, 1996͒. Perception of voiced versus voiceless consonants thus follows the regularities of speech production. Much has been made of this correspondence and a good deal of speculation has surrounded the question of why f 0 and VOT covary in speech production ͑e.g., Kingston and Diehl, 1994͒.…”
Section: Introductionmentioning
confidence: 99%
“…Following a differ ent line of argumentation, Kohler [1985] proposes that the perceptual influence of F0 reflects a production-perception relation ship. However, appropriate production data on preplosive F0 are either extremely scarce [for two speakers in Kohler, 1982] or inconsistent [Gruenenfelder and Pisoni, 1980], This might be due to the fact that microprosodic effects in preconsonantal vowels, if they exist at all, are easily over ridden by macroprosodic variations of the global sentence contour, but we could pur sue this question further by looking for a possibility of investigating the perceptual influence of F0 variations while avoiding the fortis/lenis test paradigm. A viable proposal would be to focus on a phonologically short versus long German vowel be fore a consonant which is not specified as fortis/lenis (e.g.…”
Section: Effects O F Fn Contour Variationsmentioning
confidence: 99%
“…This effect might be ex plained by hypothesizing a subjectively longer vowel duration associated with a stronger F0 movement. The longer duration would, in turn, bias the phoneme judge ments towards more lenis percepts [Lehiste, 1976;Lehiste and Shockey, 1980;Gruenenfelder and Pisoni, 1980]. Following a differ ent line of argumentation, Kohler [1985] proposes that the perceptual influence of F0 reflects a production-perception relation ship.…”
Section: Effects O F Fn Contour Variationsmentioning
confidence: 99%
See 1 more Smart Citation